「センヨウ カンソクセン ニ ヨル カイヨウ カンソク ニ カンスル ケンキュウ ショウシュウカイ」 ホウコク -ダイ43ジタイ ホウコク オヨビ ダイ44ジタイ カンソク ケイカク- - 小達, 恒夫; オダテ, ツネオ; 福地, 光男; フクチ, ミツオ; Odate, Tsuneo; Fukuchi, Mitsuo (2002)
P(論文) 「専用観測船による海洋観測に関する研究小集会」を、国立極地研究所講堂において2002年6月19日～20日に開催した。参加者は30名であった。第1日目には、第43次日本南極地域観測隊(43rd Japanese Antarctic Research Expedition, JARE-43)「専用観測船-タンガロア号」航海で実施された観測成果報告が行われた。これらデータの速報的公表の機会として、2002年10月に予定されている日本海洋学会秋季大会でシンポジウムを開催することになった。また、2002年12月の極域生物シンポジウムでは、更に解析の進んだ成果を発表することとした。第2日目には、JARE-44における「専用観測船」観測計画が検討された。JARE-44の「専用観測船」による観測計画は、2002年10月～11月に実施されるオーストラリア南極観測隊の「オーロラ・オーストラリス号」の航海、2003年1月～2月に実施される東京大学水産大学「海鷹丸」の航海に続くもので、対象海域での時系列データを取得する上でまたとない機会である。なお、同海域には3月中旬にJARE-44の「しらせ」が立ち寄ることになっている。本研究小集会では、JARE-43の結果を踏まえ、東経140度の南緯65度以南の海域で、生態系構造が異なる2観測点で集中的な観測を行い、生物生産過程と地球規模気候変化に関連した研究を行う。また、南極底層水の生成過程に関する研究を行うことになった。 A workshop on "Marine Science Program using a Charter Research Vessel" was held on 19th and 20th June 2002 at the National Institute of Polar Research (NIPR), Tokyo, with 30 participants. On the first day, scientific activities during the cruise of RV Tangaroa, chartered by the 43rd Japanese Antarctic Research Expedition (JARE), were reported. These activities will be reported at the symposium of the Oceanographic Society of Japan in October 2002. Further detail results will be discussed at the 25th Symposium on Polar Biology at NIPR in December 2002. On the second day, science plans for JARE-44, which will charter a research vessel again, were discussed. During 2002/2003 season, the "Aurora Australis", Australian National Antarctic Research Expedition, and the "Umitaka Maru", Tokyo University of Fisheries, plan research cruises in the same sea area as the JARE charter ship, in October - November 2002 and January - February 2003, respectively. "Shirase" will pass through the area in March 2003. Consequently, time serial observations will be possible using these vessels. Detail observations to reveal the relationship between biological processes and global climate change will be conducted along 140oE south of 65oS, where two different ecological structures were observed during the cruise of JARE-43. In addition to these observations, formation of the Antarctic bottom water will be ...